Beneath the heartstrings (about highly sensitive people) - Iffah Qistina Irwan (Nanyang Technological University, 2021)
‘Beneath The Heartstrings’ derived from the fact that deep within every mankind there’s an innate ability to respond to external stimuli, hence being sensitive. However, only about 15 to 20% of the human population are highly sensitive. They are born with Highly Sensitive Personality (HSP), a personality tied to high sensory-processing sensitivity (SPS) trait. Those that are characterised with this trait show heightened awareness of and subtle stimuli. Hence due to their greater sensitivity to environmental and social stimuli, they are more reactive to both positive and negative stimuli. It is why they often react differently and undergo different experiences compared to others in the same scenario and thus, get misunderstood very easily. This project dedicates itself to shedding light on the high sensory-processing sensitivity (SPS) trait, in hopes that society will be more understanding of HSP(s) (highly sensitive people) by letting people experience what HSPs experience with a focus on touch, emotions and light (human aura).